The need preservation of library materials : digitization - Skaik, Huda; Hassan, Basri; Wan Mamat, Wan Ali (IIUM Press, 2011)
In today's world of electronic information, librarians have directed their attention and efforts towards digitization. Digitization has been widely used as a method for conserving libraries' collection, in particular the special collections of rare books, manuscripts and archivals. Conversion to a digital format gives the users a new range of search tools, since what is created is a file that can be manipulated as any other electric data file.